ESKALASI KONFLIK INTERNAL SOMALIA PASCA BERDIRINYA ICU (ISLAMIC COURTS UNION) TAHUN 2000-2007 - Mia Pradita Ningrum (HI 16 UMY 020, 2016)
*20 This article tries to explain escalation of Somalia’s internal conflict after the establishment of ICU (Islamic Courts Union) in 2000-2007. Conflict escalation happened in Somalia since the establishment of Islamic Courts Union in 2000. Islamic Courts Union is a group of Islamic Court that united in one to create stabilization of economic and politic’s sector of Somalia by apply the syariah law to Somalia. Conflict in Somalia decreased for 6 month in 2006 after ICU toke the power of Mogadishu from warlord. And ICU got the legitimation from Somalia’s society since its success to decrease criminality in Somalia. But after that 6 moth of peace Somalia, a war happened again and the conflict was escalated. The success of ICU did not really success. Therefore some groups in internal Somali’s people were against ICU and intervention of other country were happen to destroy the ICU’s power in Somalia